Characteristics of Zuhud or Asceticism in The Quran - Sri Astuti (Universitas Ahmad Dahlan, 2022)
This article discusses the study of thematic interpretation (mawḍū‘ī) methodologically. The mawḍū'ī method is to collect verses of the Qur'an related to one topic or one goal. The thematic approach in understanding the verses of the Qur'an is to understand the meaning contained in the verse by studying other traditions related to the same topic of discussion and paying attention to their respective correlations so that a complete understanding is obtained.One of the topics that the author will discuss is zuhud. The definition of zuhud according to the Big Indonesian Dictionary is about leaving the world; Hermitage According to Sufyan bin Uyaynah, zuhud is divided into three letters, namely Za', Ha', and Dal. It means Za' is tarku az-Zina (leaving adultery), Ha' is tarku al-Hawa (leaving lust), and Dal is tarku al-Dunya (leaving the world). Meanwhile, according to Ibn Taymiyyah, zuhud is eliminating desire (desire) and eliminating hatred for something.Based on the understanding of zuhud mentioned by Imam Ghazali, generally it is the answer of most people regarding zuhud which will focus on Sufism. Some people also think that zuhud is only limited to leaving wealth, because leaving wealth and showing poverty is an easy thing for anyone who wants to say that he is a zahid. Actually zuhud is an attitude of sincerity in the heart towards the limitations and advantages one has. However, there are many different opinions regarding the meaning and practitioners of zuhud itself. Therefore, this paper intends to examine the meaning of zuhud more deeply by bringing in verses from the Qur'an and related traditions through the study of thematic interpretation.